Aulas de língua portuguesa no ensino médio : contexto, interações e ensino em uma escola pública de Marau/RS - Brandoli, Fernanda Maria (2013)
The School, in Brazil, has been the target of much criticism regarding its quality, especially by the media who persistently exhibit reports on failure rates and ineffective student learning on this level. It is clear, however, that despite the constant exposure in the media, remain poorly explored the interactions that occur in the classroom and learning pathways and development of students. Thus, this thesis addresses a field survey conducted with 14 students in the first year of high school, during the second half of 2012, a state school in the municipality of Marau Rio Grande do Sul Referring to intellectual development by through social interactions, Lev Vygotsky and the philosophy of language Mikhail Bakhtin, the research objectives are to analyze the quality of the interactions that occur in the classroom, in order to provide elements for understanding how the process of teaching and learning the tongue is becoming an organized environment intentionally for this purpose. So, were mobilized some methodological strategies, which offered support for collecting survey data, namely: a) the insertion of the researcher in the classroom and running ten direct observations, written and recorded in a field diary; b ) the application of a questionnaire to students as a condition to develop a profile of the group and rebuild their frustrations and expectations in relation to the school and the teaching and learning of language c) conducting semi-structured interview with the teacher of Portuguese Language seeking to understand their difficulties, expectations, relationship with students and the meanings it attaches to language teaching, finally, d) the analysis of key documents that guide the teaching of this educational institution. The findings produced in the process of the research demonstrate that the Portuguese classes the first year of high school are characterized by the prevalence of content and grammatical exercises fixation, however, both pupils and teaching itself, recognize the difficulties of the class in relation reading, comprehension and text production. The survey results point also to the need to know school searched your reality and rethink the structure and dynamics of Portuguese classes in high school, in order to overcome difficulties and improve the quality of interactions and relationships education that occur in the classroom, thus contributing to better training of students and reduce high failure rates